Corregir letras para unir espíritus. Los jesuitas y las cartas edificantes en el Portugal del siglo XVI - Palomo, Federico (Cuadernos de Historia Moderna, 2006)
Since its foundation, in 1540, a complex system of flowing information inside the new Order was promptly launched by the Society of Jesus. Letters became not only an important tool in order to built its powerful and bureaucratic machine but they were also regarded as a method for connecting the diverse Jesuit communities. The diffusion of apostolic action models and edifying news was maintained by a controlled epistolographic exchange and this contributed to reinforce a common religious identity among Jesuits. This paper is devoted to improving our comprehension about this specific aim of Jesuit letters and firstly focuses on some aspects related to the framework where these edification letters were elaborated; secondly, the reiterative use of specific narrative structures, precise spiritual references and apostolic images re highlighted; finally, this essay attempts to draw attention to the ffects that the letters encouraged in the particular nvironment of both reception and appropriation of he Portuguese Jesuit communities during the second half of 16th century.